High Performance Liquid Chromatography - Recent Advances and Applications 2023
DOI: 10.5772/intechopen.110035
|View full text |Cite
|
Sign up to set email alerts
|

Green Strategies toward Eco-Friendly HPLC Methods in Pharma Analysis

Abstract: The global need for changing the processes in order to meet the green analytical chemistry (GAC) criteria is a great challenge for the pharmaceutical industry. High-performance liquid chromatography (HPLC), as one of the most frequently used techniques in various stages in the pharmaceutical industry, generates huge amounts of organic toxic waste. Therefore, the implementation of the GAC principles in pharma analysis is highly required. Although the number of published papers concerning green chromatography ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…To achieve this, the first step of the method development was to replace the organic solvents (MeOH and ACN) in the mobile phase of the conventional (referent) USP method with EtOH, an environmentally friendly solvent. 2,3 Considering that the organic solvent content in the reference method was 60 % and EtOH has higher elution strength than ACN and MeOH, the preliminary investigations started with the mobile phase containing 50 % EtOH. Considering that the pKa value for diazepam is 3.4, 5 and the pH value of the mobile phase (H2O: EtOH, 50:50, v/v %) is 6.5, these chromatographic conditions allowed for ionization of the DZP molecule with acceptable retention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve this, the first step of the method development was to replace the organic solvents (MeOH and ACN) in the mobile phase of the conventional (referent) USP method with EtOH, an environmentally friendly solvent. 2,3 Considering that the organic solvent content in the reference method was 60 % and EtOH has higher elution strength than ACN and MeOH, the preliminary investigations started with the mobile phase containing 50 % EtOH. Considering that the pKa value for diazepam is 3.4, 5 and the pH value of the mobile phase (H2O: EtOH, 50:50, v/v %) is 6.5, these chromatographic conditions allowed for ionization of the DZP molecule with acceptable retention.…”
Section: Resultsmentioning
confidence: 99%
“…1 The implementation of the GAC principles in the process of green chromatographic method development, as well as the transfer of the conventional HPLC methods into ecofriendly solutions, is an essential part of the development strategy in the pharmaceutical industry. 2 In particular, GAC principles play a crucial role in the modern industry's development strategy. Reverse phase high-performance liquid chromatography (RP-HPLC) is the most commonly employed technique in pharmaceutical quality control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GAC principles were recognized by scientists, researchers, and analysts, leading to an increase in papers published in various GAC fields (fundamentals, spectroscopy, electrochemistry, and separation methods) [5]. The pharmaceutical industry is facing a global need to change activities to meet GAC measures, as a study exposed by McMaster University in 2019 showed that it emits more greenhouse gases than the automotive production sector [6]. The pharmaceutical industry places various emphases on pharma analysis, and HPLC is one of the most often utilized methods.…”
Section: Introductionmentioning
confidence: 99%
“…Green Analytical Chemistry (GAC) is an effort to find workable solutions to off-line waste management in order to replace dirty practices with hygienic ones [6].…”
Section: Introductionmentioning
confidence: 99%